HPV16 and HPV52 E6-specific immunity in infected adults on combination antiretroviral therapy / Leng Chan Yoon - Leng , Chan Yoon (2017)
Human papillomavirus (IIPV) infection and its associated cancers disproportionately affect those infected with human immunodeficiency virus (HIV) despite effective combination antiretroviral therapy (cART). Cell-mediated immune (CMI) responses against HPV E6 antigen have been associated with clearance of HPV infection or its associated diseases. This study aims to investigate the presence of IIPV 16 and 52 E6- specific T cell responses in HIV+ patients on cART with suboptimal (siR) and optimal (olR) immune reconstitution. A cross-sectional cohort (n= 67) consisting of patients with siR (CD4+ T cell <350cells/mm3) and oiR (CD4+ T cell >500cells/mm3) after a minimum of2-years on cART with sustained suppressive viral load RNA <50copies/ml over a year following cART were recruited from Infectious Diseases clinic in University of Malaya Medical Centre (UMMC). A detailed questionnaire on socio-demographic information was administered. Specimens obtained from each participant included whole blood, an anal swab and oral rinse. HPV DNA genotyping test was performed on anal and oral specimens. Anal cytology was also undertaken. Peripheral blood mononuclear cells (PBMCs) were isolated from whole blood for interferon (IFN)-y ELISPOT and flow cytornetry. IFNy ELISPOT was used to detected IIPV16 and IIPV52 E6-specific T cell immune responses whereas flow cytometry was to identify the immunophenotypes of CD4+ and CD8+T cells at systemic level. All IllY+ individuals received non-nucleoside reverse transcriptase inhibitors (NNRTI)-based cART. As compared to olR group, siR group exhibited lower baseline of CD4+ T cell count (28 vs 190cells/mm3, p<O.OOl), CD8+ T cell count (473 vs 7Jlcells/mm\ p=O.Oll) and CD4/CD8 ratio (0.07 vs 0.22, p<O.OOl). Those in the siR group had more AIDS-defining illnesses compared to oiR group (84.4% vs 54.3%, p-0.008). Despite suppressive viral load, siR showed higher percentage of CD4+ central memory T cell (TcM) ( 46.2% vs 38.1 %, p<0.05) and effector memory T cell (Tl·f\t) in both CD4+ (26.8% vs 19.0%, p 0.00 I) and CD8+ (56.1% vs 43.6%, p<0.05) subsets, with lower naYve CD4+ (24.9% vs 36.4%, p<0.05) and CD8+ (8.1% vs 1 5.7%, p<0.05) T cells compared to those with oiR. In addition, higher percentage of regulatory T cells (Treg), activated and senescent CD4+ and CD8+ T cells were observed in siR compared to olR groups. The prevalence of oral ( 16.7 vs 1 1.1 %, p=0.57) and anal (57.1% vs 56.5%, p=0.97) HPV DNA between siR and oiR groups were similar. In multivariate analysis, age of cART initiation (OR= 1.21 [95% CI 1.04-1.40], p=O.Ol), and serum llsCRP level (OR=908 [95% CI 4.3-19 1720], p=O.Ol) were risk factors correlating to anal HPV carriage. Furthcm1ore, siR (2/32, 6.3%) had sjgnificant lower HPV16 and 52 E6-specific CMI responses compared to oiR (9/34, 26.5%) (p=0.028) irrespective of anal and oraiiiPV carriage. Apart from CD4+T cell counts, no other immunological correlates to HPV 16 and 52 E6-specific T cell responses. As a conclusion, a longitudinal study to evaluate the effect of HPV 16 and 52-specific CMI responses among HIV+ adult with optimal immune reconstitution is recommended. Clinically, anal screening is recommended for II IV+ population, particularly those with poor immune reconstitution.